A Quantitative Model for Alkane Nucleophilicity Based on C−H Bond Structural/Topological Descriptors. Issue 8 (21st January 2020) - Besora, Maria; Olmos, Andrea; Gava, Riccardo; Noverges, Bárbara; Asensio, Gregorio; Caballero, Ana; Maseras, Feliu; Pérez, Pedro J.
Abstract: A first quantitative model for calculating the nucleophilicity of alkanes is described. A statistical treatment was applied to the analysis of the reactivity of 29 different alkane C−H bonds towards in situ generated metal carbene electrophiles. The correlation of the recently reported experimental reactivity with two different sets of descriptors comprising a total of 86 parameters was studied, resulting in the quantitative descriptor‐based alkane nucleophilicity (QDEAN) model. This model consists of an equation with only six structural/topological descriptors, and reproduces the relative reactivity of the alkane C−H bonds. This reactivity can be calculated from parameters emerging from the schematic drawing of the alkane and a simple set of sums. Abstract : The QDEAN model constitutes a first approach to the quantitative modeling of the reactivity of alkane C−H bonds towards electrophiles. A remarkable correlation between experimental and calculated values was achieved with just six topological descriptors for the C−H bonds under evaluation.